Effect of Sintering Temperature on Functionally Graded Nickel/Alumina Plate - Latiff, M. I. A.; Jamaludin, S. N. S.; Basri, S.; Hussain, A.; Alothmany, D. S.; Mustapha, F.; Nuruzzaman, D. M.; Ismail, N. M.; Ismail, I. (Trans Tech Publication, 2014)

(untitled)
Functionally graded material that consists of gradually changed dual-phase compositions along the thickness direction of its structure has been introduced as an answer to sharp interfaces problems occur while the processing. Because the sintering temperature is one of the factors that affects the response of the functionally graded (FG) plates, this paper is presented to show the domination of the consolidation parameter on the stress field of the plates. A two-dimensional structural model of an 8-node element is used in the simulation of the residual stress of the plates during cooling from 1200ºC and 1350ºC to room temperature during sintering. The residual stress distribution calculated from the present results are examined thoroughly in order to validate the simulation method and to compare them with the established results. In order to observe the morphological and shrinkage due to the sintering process, the Ni/Al2O3 FG samples were manufactured via powder metallurgy routes under argon atmosphere. This study reveals that the sintering temperature does affects the sintering behaviors including the microstructures and radial dimensions of the FG plates. The numerical simulation is found to be useful to predict the stress concentration area within the structures and consequently improve the design of the FG plates.